2024
DOI: 10.5455/medarh.2024.78.105-111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calprotectin, IL-6, and CRP in Distinguishing Between Inflammatory Bowel Disease and Diarrhea Predominant Irritable Bowel Syndrome

Bui Huong,
No author No author,
Nguyen Hien
et al.

Abstract: Background: The early establishment of prophylaxis and immediate administration of anticoagulant therapy upon the diagnosis of venous thromboembolism should be the treatment objectives in these patients. Objective: The study aimed to determine the optimal cut-off point of Calprotectin, IL-6 (interleukin-6), CRP (C reactive protein) to differentiate UC, IBS-D. Methods: A cross-sectional descriptive study of 335 individuals ≥15 years old was performed, including 31 healthy controls, 215 with IBS-D, 71 diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, a positive diagnosis of irritable bowel syndrome can be made based on the evaluation of gastrointestinal symptoms (especially alarm signs), normal colonic mucosa [3,4], and the use of the symptom-based Rome IV criteria [5]. Very recent study clearly showed that the Calprotectin immunoassay has the best value in discriminating between IBD and diarrhea-predominant irritable bowel syndrome [6]. An effective serum biomarker other than the routine measurement of patients' C-reactive protein (CRP) is thus desired as a diagnostic tool to predict the presence or absence of IBD or other forms of colitis in outpatient clinics at individuals' initial visits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a positive diagnosis of irritable bowel syndrome can be made based on the evaluation of gastrointestinal symptoms (especially alarm signs), normal colonic mucosa [3,4], and the use of the symptom-based Rome IV criteria [5]. Very recent study clearly showed that the Calprotectin immunoassay has the best value in discriminating between IBD and diarrhea-predominant irritable bowel syndrome [6]. An effective serum biomarker other than the routine measurement of patients' C-reactive protein (CRP) is thus desired as a diagnostic tool to predict the presence or absence of IBD or other forms of colitis in outpatient clinics at individuals' initial visits.…”
Section: Introductionmentioning
confidence: 99%